Solar/EM energy harvester for autonomous operation of a monitoring sensor platform. Issue 1 (March 2014) - Niotaki, Kyriaki; Giuppi, Francesco; Georgiadis, Apostolos; Collado, Ana
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, a hybrid solar/electromagnetic (EM) energy harvester that operates at 2.45 GHz is presented. The proposed harvester integrates the solar cells in the same area as the rectenna element obtaining a compact implementation. The radiating element that forms part of the rectenna is a cavity-backed slot antenna based on substrate-integrated waveguide technology, which allows for a compact, single substrate implementation. The radiating element is connected to a circuit that provides both the rectification of the incoming EM signals and the collection of DC energy coming from solar cells. A single-substrate prototype has been implemented, demonstrating an overall power conversion efficiency up to 30%, depending on the incoming radio frequency signal level and the ambient light conditions.